TINJAUAN HISTORIS PERKEMBANGAN SISTEM PERBANKAN SYARIAH DI INDONESIA - rahayu, eka; Prastika, Rima; Sanawati, Ciptia Khoirulina (Commodity : Jurnal Perbankan dan Keuangan Islam, 2023)
Sharia banks were developed based on the desire to provide financial transaction services that are in line with moral values ​​and principles of Islamic law amidst the proliferation of conventional banks which are synonymous with usury, maisir and gharar. The initial presence of sharia banking is expected to be the main solution for financial facilities and poverty alleviation without compromising sharia principles. The sharia banking system continues to develop, especially in Indonesia, although it seems to be slower than other countries. The idea of ​​sharia banking began to emerge in 1990 with the implementation of a workshop by the MUI (Indonesian Ulema Council). Subsequently, it was legalized in 1992 with the issuance of Law No. 7 of 1992 which was then deregulated in 1998 with explicit provisions regarding the permissibility of the dual banking system. The full existence of sharia banking was recognized after the passing of Law no. 21 of 2008 concerning sharia banking which specifically regulates institutions and business activities and the codification of banking products. Based on the OJK (Financial Services Authority) report in quantity, sharia banking has increased with the number of banks consisting of 13 BUS, 21 UUS and 166 BPRS. Sharia banking has also experienced a downward trend in its development. This is because the operational system of Islamic banks still adopts the conventional banking system with the characteristics of still prioritizing profit orientation and still referring to interest rates. The development of sharia banks must also be supported by competent and professional HR (human resources), commitment to 100% implementation of sharia principles, and also responsive marketing that is able to grow public trust in sharia banks.